Seroprevalence of Leptospira spp. in Horses in Israel - Tirosh-Levy, Sharon (Pathogens, 2021)
Leptospirosis has been reported in both humans and animals in Israel but has not been reported in horses. In 2018, an outbreak of Leptospira spp. serogroup Pomona was reported in humans and cattle in Israel. In horses, leptospirosis may cause equine recurrent uveitis (ERU). This report describes the first identification of Leptospira serogroup Pomona as the probable cause of ERU in horses in Israel, followed by an epidemiological investigation of equine exposure in the area. Serologic exposure to Leptospira was determined by microscopic agglutination test (MAT) using eight serovars. In 2017, serovar Pomona was identified in a mare with signs of ERU. Seven of thirteen horses from that farm were seropositive for serogroup Pomona, of which three had signs of ERU. During the same time period, 14/70 horses from three other farms were positive for serogroup Pomona. In 2015, two years prior to this diagnosis, 259 horses from 21 farms were sampled and one horse tested seropositive for serovar Icterohaemorrhagiae. In 2018, one year later, 337 horses were sampled on 29 farms, with none testing seropositive. Although horses are not considered a major host of Leptospira spp., it appears that horses may be infected, and clinically affected, in the course of an outbreak in other species. The identification of leptospirosis in stabled horses may impose a significant zoonotic risk to people.